Associations Between Family Risk Factors and Child Neglect Types in U.S. Army Communities. (February 2019) - Cozza, Stephen J.; Ogle, Christin M.; Fisher, Joscelyn E.; Zhou, Jing; Whaley, Gloria L.; Fullerton, Carol S.; Ursano, Robert J.
Recent theory and empirical research suggest that child neglect is a heterogeneous phenomenon characterized by various types. This study examined family risk factors associated with five neglect types including failure to provide physical needs, lack of supervision, emotional neglect, moral–legal neglect, and educational neglect in 390 substantiated cases of neglect in four U.S. Army communities. Family factors associated with elevated risk of each neglect type relative to other types were identified using multivariate regression. Relatively distinct sets of family risk factors were differentially associated with the neglect types. Family mental health problems and larger family size were associated with risk of failure to provide physical needs, childcare problems and larger family size were associated with risk of supervisory neglect, and family disagreements were associated with risk of emotional neglect. None of the family factors were associated with elevated risk of moral–legal or educational neglect. Results can inform the development of indicated and relapse prevention strategies for families affected by different neglect types.